Disponibilidade hídrica no crescimento, acúmulo e composição química do óleo essencial de Mentha piperita e estudo comparativo de atividades antioxidantes em espécies de mentas - Lordêllo, Diogo Mendes da Silva (2015)
In the first article aimed to evaluate the vegetative growth of M. piperita grown under different water availability, as well as its influence on the chemical composition accumulation and antioxidant activity in vitro of the essential oil were 4 treatments: (T1) 100-85% capacity field (CC); (T2) 80-65% DC; (T3) 60-45% of C; (T4) 40-25% of CC with 5 blocks. The plants were maintained for 30 days in DC and under treatment for 40 days. Evaluated the vegetative growth beyond the essential oil from the leaves which was extracted by hydrodistillation, analyzed by GC-FID and GC-MS and quantified its antioxidant potential. At the 40% level of DC there was a significant reduction in the MSF input MSC 31% and 15.6%, also changing the chemical composition of the essential oil. The level of 40% moisture was elevated total antioxidant capacity and 80% increase of the chelating power of the oils. In the second article aimed to quantify the total phenolics and compare the antioxidant potential in vitro aqueous and hydroalcoholic of M. piperita, M. villosa and M. rotundifolia. The aqueous extracts were prepared under reflux for 60 minutes at a concentration of 5%. The hydroalcoholic extracts were prepared by sonication in 70% ethanol for 30 min at 5% concentration. The quantification of total phenolics, flavonoids and dihidroflavonoides were performed by spectrophotometry. The antioxidant activity was evaluated by the total antioxidant activity methods by reducing ammonium molybdate, chelating power, reducing power, scavenging activity of free radicals (ABTS and DPPH). Regardless of the kind of Mentha and liquid extractor, the content of phenolics, flavonoids and dihidroflavonoides were higher in the leaves than in stems. Positive correlation between levels of phenolic compounds and antioxidant responses in vitro activity were more pronounced in hydroalcoholic extracts of the leaves. The greatest antioxidant activities were recorded in hydroalcoholic extracts of leaves of mint.